Students’ perception & awareness on SDG programmes at the Centre for Foundation Studies IIUM - Ng Ban Choi, Muhammad Ng Chee Hong; Teruk, Kamaril Azlah; Mohd Nasohah, Nor Sa'adah; Zubir, Nazira; Zahari, Shafiyyah Solehah (CENTRE FOR FOUNDATION STUDIES IIUM, 2024)
Malaysia adopted the 2030 Agenda for Sustainable Development goals (SDGSs) at the United Nations General Assembly in New York on 25 September 2015 which outlines 17 sustainable development goals with 169 associated targets that are integrated and indivisible. IIUM’s Sejahtera Academic Framework, (SAF) aligns with the SDGs by emphasizing sustainable development, social justice, and holistic well-being. SAF provides a localized lens through which IIUM students approach sustainable development, ensuring their efforts align with global goals. Therefore, students in the Centre for Foundation Studies (CFS), IIUM initiated and proposed programmes that align with the SAF principles. The awareness and involvement of students in SDG programmes in CFS IIUM are critical to nurture future leaders who can bring changes to the world. The study showed that students’ awareness of the importance of SDG is high, and they were interested in joining SDG programmes. However, the participation in the SDG programmes in CFS IIUM is only moderate